Design and development of automated token assembly system - Khaw, Jia Ying (2021)
Considering the COVID-19 outbreak globally, assembly machines are relativelyimportant for manufacturing sectors for mass production and process reliability. Human errors are the key factor that gives rise to diminishing the quality of thefinal product in the existing manual assembly operations. Considering this issue, it becameapparent that the new assembly methods should be adapted. The aimof this project isto design an automated assembly system that is able to assemble the door gift. Theautomated assembly system is made up of three body magazines, a key magazine, linear actuators, a gripper, and a main assembly acrylic board. Aluminumprofilesareimplemented as the machine frame due to their extraordinary flexibilityandstructural strength. This industrial-based project is linked with Greatech Integration(M) Sdn. Bhd. The assembly machines provide a significant contribution tothefieldof industrial automation and robotics with the integration of an automated assemblysystem that can assemble door gifts. The future implementation of the automatedassembly system offers leading advantages in refilling components as the pillars anddrum can be removed with the empty magazines. Hence, the objectives of enhancingthe reliability of assembly lines with lesser human labor and time requiredareachieved.